STICK HALO BERBAHAN DASAR HATI AYAM DAN TEPUNG KACANG TOLO (Vignia unguiculata L.) SEBAGAI MAKANAN SELINGAN SUMBER ZAT BESI DAN PROTEIN BAGI REMAJA PUTRI ANEMIA - Nanda Maedy, Anggun Puspita; Fitria, Mona (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2023)
The World Health Organization (WHO) states that more than 30% or 2 billion people in the world are anemic. Adolescents are one of the groups that are vulnerable to iron deficiency anemia, especially adolescent girls. One effective strategy to prevent and control the incidence of iron deficiency anemia in adolescent girls besides using iron-enriching tablets is to conduct food-based interventions rich in iron from local food ingredients such as chicken liver and tolo beans. The purpose of this study was to obtain the formulation of chicken liver and tolo bean flour on the quality of Stick Halo snacks, to determine the effect of chicken liver and tolo bean flour formulations on organoleptic properties, nutrient content (energy, protein, fat, carbohydrates and iron) and production costs. The design of the experimental study with a sample size of 30 fairly trained panelists for organoleptic tests. The results of the study on the organoleptic properties of the three formulas concluded that there was a significant effect (p value <0.05) on taste, and there was no effect of chicken liver and tolo bean flour formulations on aroma, color, taste, texture and overall stick (p value> 0.05). Formula 2 is the best formula preferred by panelists. The results of the proximate test obtained nutritional value per serving (65 g) and fulfillment of AKG per day, namely energy 309 kcal (15%), protein 9 grams (14%), fat 17 grams (25%), carbohydrates 31 grams (10%), iron 4 mg (25%). The production cost of one serving (65 grams) of Stick Halo is IDR 7.004. Further research is needed regarding the shelf life of Stick products and the need to add high-protein ingredients to increase the iron and protein values ​​in Stick products.